Culturally informed and flexible family based treatment for adolescents: enhancements to better serve adolescents with self-harm behavior - Mena, Maite P.; del Rey, Gabrielle M.; Gutierrez, Melissa A.; Gattamorta, Karina A.; Lazarus, Rebecca A.; Santisteban, Daniel A. (Frontiers in Child and Adolescent Psychiatry, 2025)
Culturally Informed and Flexible Family Based Treatment for Adolescents (CIFFTA) is a manualized treatment that has been shown to reduce youth substance misuse and a variety of behavior problems but it has not been used to treat self-harm behavior in youth. The purpose of this manuscript is to describe enhancements that can address the treatment needs of diverse youth reporting suicide risk, cutting, and other self-harming behavior. We describe the enhancements to psychoeducational, individual therapy and family therapy content and processes as well as technological enhancements to improve access to treatment and to engage the adolescent in therapeutic work between therapy sessions. We believe that to help reduce barriers to service utilization in diverse populations, the treatment must also be ecologically valid. We present the case of a 15 year old Latine female who received treatment for cutting behavior and demonstrate CIFFTA's components in action. As we have reported separately, the acceptability of this enhanced intervention is supported by data showing that 93% of the youth and families attended at least 8 sessions and that on average they received over 23 sessions of treatment. This treatment enhancement effort resulted in new tools that were integrated into the manualized CIFFTA making it easier to engage families and deliver interventions. These enhancements culminated in an adaptive, replicable, and culturally informed treatment for diverse youth reporting self-harm and their families.